Pulmonary Embolism: Still a Diagnostic Quandary (Journal of Armed Forces Medical College, Bangladesh, 2011)
Objectives: The objective was to review the progress made in the diagnosis of pulmonary embolism over the past decade and the future direction of diagnostic modalities. Methods: Research studies, review articles and scientific meeting abstracts published were reviewed. Results: Significant progress has been made in the diagnosis of pulmonary embolism. Strategies have been developed to increase the sensitivity and specificity of the diagnostic tools. Conclusion: With the advances of the technology and better understanding of patho-physiology, offer the hope of improving the medical management of common and potentially life threatening condition like pulmonary embolism. Key words: Pulmonary embolism; diagnostic modalities; progress DOI: http://dx.doi.org/10.3329/jafmc.v7i1.8625 JAFMC Bangladesh. Vol 7, No 1 (June) 2011; 34-40